Analisis Kinerja Karyawan Menggunakan Gaya Kepemimpinan dan Self Efficacy - hery sahrial; Sunaryo Sunaryo (Universitas Harapan Medan, 2021)
The purpose of this study was to analyze employee performance by using the variables of leadership style and self efficacy. This research was conducted at a motor vehicle distributor company in the city of Medan. The sample of this study was 123 people. This research is a survey research using a questionnaire. Data analysis using Structure Equation Modeling (SEM). The results showed that leadership style and self-efficacy are variables that have a significant impact on employee performance. Self Efficacy is the most dominant variable affecting employee performance.